Perceptions and predictors of patient safety culture among nurses working in a hospital in Muar, Johor, Malaysia - Tan, Goek Eng (2019)
Patient safety culture is an important working culture among healthcare professionals to provide quality care to patients. Low levels of patient safety culture are associated with a series of serious medical errors such as medication error, hospital-acquired infection and fall. As nurses are always in contact with patients to provide nursing care, high levels of patient safety culture can minimize or prevent medical errors. To the best of knowledge, limited study has explored the perceptions of patient safety culture among Malaysian nurses. Thus, this study is aimed to examine the perceptions of patient safety culture among nurses working in Muar Hospital. The data were collected from 250 nurses working at Hospital Muar by using stratified simple random sampling. Respondents were registered nurses, assistant nurses (jururawat masyarakat), nurse educators, nursing managers (sisters) and senior nursing managers (matrons) from various clinical settings, including both acute and non-acute setting. Hospital Survey on Patient Safety Culture (HSPSC) was utilised to measure the perceptions of patient safety culture among nurses. Descriptive statistics were analysed to identify the demographic characteristics of the sample and to examine the average positive response of each patient safety domain. Pearson’s correlation was utilized to examine the bivariate correlations among variables and multiple regression was used to identify the predictors of overall perceptions of patient safety and frequency of events reported. Results showed that the mean age of respondents was 36.2 ± 7.89 years. The majority were Malay (99.6%) and women (96.8%). More than half of the subjects were registered nurses (79.2%). Descriptive analysis indicates that the dimension of “organizational learning— continuous improvement” was most practiced (78.4%) while “non-punitive response to errors” was least practiced (11.6%) by the nurses. Pearson’s correlation showed that “teamwork within units”, “supervisor/manager expectations and actions promoting patient safety”, “management support for patient safety”, “feedback and communication about error”, “teamwork across units”, “handoffs and transitions”, and the number of year(s) working as a nurse” were all positively correlated with the overall perception of patient safety (all r<0.3, p>0.05). Multiple regression analysis found that nurses in the acute setting had higher overall perceptions of patient safety culture. Furthermore, “supervisor/manager expectations and actions promoting patient safety”, “feedback and communication about error”, “handoffs and transitions”, and “communication openness” positively predicted the overall perceptions of patient safety culture with R² of 0.192. On the other hand, “feedback and communication about error”, “handoffs and transitions”, “communication openness” and “staffing” were negatively predicted frequency of events reported with R² of 0.136. Thus, findings of this study suggest further investigation, especially in several dimensions that were found improve patient safety culture level among nurses.